Bean Plataspid: Megacopta cribraria (Fabricius) (Insecta: Hemiptera: Heteroptera: Plataspidae) - Ashley Poplin; Amanda Hodges (EDIS)
Also known as the kudzu bug, lablab bug, and globular stink bug, the bean plantaspid is native to Asia, where it is not an agricultural pest. But in the U. S., it is reported as a pest of soybean in Georgia and South Carolina. Adults from established populations overwinter on light colored structures, in leaf litter, and underneath the bark of trees. Also, like stink bugs, adults tend to excrete an odor as a defense mechanism when disturbed. The defense chemical these insects secrete may stain the surface of the house, building or vehicle where aggregation occurs. This 6-page fact sheet was written by Ashley Poplin and Amanda Hodges, and published by the UF Department of Entomology and Nematology, June 2012.